The dynamic of the Iron-age village: A technique for the relative-chronological analysis of area-excavated Iron-age settlements - K., Mads (Journal of Danish Archaeology, 1997)
The dynamic of the Iron-age village: A technique for the relative-chronological analysis of area-excavated Iron-age settlements